Did the UK policy response to Covid-19 protect household incomes? - Mike Brewer; Iva Valentinova Tasseva (University of Essex, Institute for Social and Economic Research (ISER), 2020)
We analyse the UK policy response to Covid-19 and its impact on household incomes, as of late April 2020, using microsimulation methods. We estimate that households will lose a substantial share of their net income (8% on average). The proportional losses are largest for higher-income families. However, the overall impact of the crisis on income inequality is small. Earnings subsidies (Coronavirus Job Retention Scheme) will protect household finances and provide the main insurance mechanism during the crisis. Besides subsidies, Covid-related benefit increases and tax-benefit automatic stabilisers will play an important role in mitigating the shocks, underlining the importance of tax-benefit design in protecting household incomes during economic downturns. Analysing how a near-decade of austerity has affected the UK safety net, we find that, even after the extra benefit spending, the ability of the 2020 system to provide insurance against the shocks would be similar to the 2011 pre-austerity system.
Keywords: D31; E24; H24; 330; Covid-19; income distribution; earnings subsidies and tax-benefit policies